К ВОПРОСУ О СУЩНОСТИ ПОНЯТИЙ «СУВЕРЕНИТЕТ» И «НЕЗАВИСИМОСТЬ». (Journal of actual problems of jurisprudence, 2016)
In this article the maintenance and significance of the categories «sovereignty» and «independence» and also their role in jurisprudence have been researched. The author analyzed the different points of view to this problem and shows the methodological role of such categories in the modern judicial science.